Cor-pulmonale: a rare presentation in a case of middle lobe syndrome - Ankit Abhishek; Sinha, Ajay Kumar; Aditya, Vikram (International Journal of Research in Medical Sciences, 2023)
Brock’s syndrome or middle lobe syndrome (MLS) is chronic or recurrent collapse of right middle lobe due to causes which may be obstructive or non obstructive. The pathogenesis is not completely understood. An expert committee of the world health organization defined cor pulmonale as hypertrophy of the right ventricle resulting from diseases affecting the function and/or structure of the lungs.” Cor pulmonale is a common heart disease and a leading cause of disability and death. We are reporting this association in a 65y old female who presented to the emergency with acute exacerbation of COPD with SpO2=64% room air. Chest X-ray and HRCT thorax showed features suggesting MLS and ECG shows features suggesting P pulmonale /right atrial enlargement. BNP too was elevated. Patient was resuscitated and put on mechanical ventilation after ABG showed respiratory acidosis. Appropriate treatment with bronchodilators and antibiotics was given.